Endothelial progenitor cells and asymmetric dimethylarginine after renal transplantation - Teplan, Vladimír; Mahrová, Andrea; Lesná, Ivana K; Racek, Jaroslav; Valkovský, Ivo; Štollová, Milena (Journal of renal nutrition, 2015)
Levels of the endogenous nitric oxide synthase inhibitor asymmetrical dimethylarginine (ADMA) are elevated and endothelial progenitor cells (EPCs) decreased in patients undergoing renal transplantation (Tx) and may contribute to cardiovascular complications. In this study, we tested the hypothesis that elevated ADMA and decreased EPC can be positively influenced with regular physical exercise early after Tx. Blood samples for analysis of ADMA and EPC were obtained from randomly selected 64 patients after Tx who agreed to participate in a supervised aerobic exercise program for 6 months (group I). Samples were collected before the training began, 1 month after surgery (with stabilized renal function), and at 6 months after initiation. Sixty-two age, sex, human leukocyte antigens (HLA) typing, duration of previous dialysis, history of cardiovascular disease, and immunosupression regimen-matched transplant patients who did not exercise regularly were examined as controls (group II). There were no differences in ADMA levels and EPC count between both groups before the training program began. After 6 months of exercise, ADMA concentration in the group I decreased (3.50 ± 0.45 vs. 2.11 ± 0.35 μmol/L; P < .01) and was also lower comparing with group II (2.11 ± 0.23 vs. 3.25 ± 0.35 μmol/L; P < .01). In the same period, EPC cells increased from 2.085 ± 650 cells/mL versus 3.991 ± 560 cells/mL, P < .01 in group I; but in group II, changes were nonsignificant (P = .11). Blood lipids, HbA1c, insulin, and systolic blood pressure were also affected by the training program. Elevated ADMA level and decreased EPC count were significantly influenced by early regular exercise in patients after Tx.
Keywords: dospělí; Prospective Studies; Kidney Transplantation; Arginine; Humans; následné studie; lidé středního věku; prospektivní studie; Middle Aged; Endothelial Progenitor Cells; transplantace ledvin; Follow-Up Studies; arginin; mužské pohlaví; Exercise Therapy; endoteliální progenitorové buňky; Adult; Postoperative Complications; terapie cvičením; ženské pohlaví; pooperační komplikace; lidé; Aged; senioři; Male; Female